2018
DOI: 10.1109/tap.2018.2874489
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Modeling of Ultrawideband Propagation Along a Wind Turbine Blade

Abstract: Full-wave numerical analysis of an ultrawideband wireless link in frequency band 3-5 GHz along a 37.3m long wind turbine blade is presented. The method used for the analysis is the well-established finite-difference time-domain (FDTD) method with staggered Yee mesh. Simulated results are compared to data obtained from measurement on a real blade, in two experiments involving antennas transmitting both from outside near the blade tip and from inside the blade. In the first experiment, when the wave is propagate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…In order to predict the link budget, we have simulated the propagation in our in-house finite-difference time-domain (FDTD) code. We have shown that despite the challenges the FDTD method is capable of delivering results that are in good agreement with measurements [2]. However, due to the enormous size of the blade (58.7 m) and necessary spatial resolution (5 mm), each simulation of the blade took 17 hours to finish.…”
Section: Introductionmentioning
confidence: 62%
“…In order to predict the link budget, we have simulated the propagation in our in-house finite-difference time-domain (FDTD) code. We have shown that despite the challenges the FDTD method is capable of delivering results that are in good agreement with measurements [2]. However, due to the enormous size of the blade (58.7 m) and necessary spatial resolution (5 mm), each simulation of the blade took 17 hours to finish.…”
Section: Introductionmentioning
confidence: 62%
“…e wave length of the electromagnetic wave plays a key role in obtaining attractive and accurate results. Greater the size of the wavelength, the more accurate the results from an RT stimulation [47,48]. Reliant on the electrogeometrical appearances available in digital maps, a ray undergoes diffuse scattering, diffraction, penetration, reflection, or attenuation.…”
Section: Simulations With the Dominant 3d Ray Tracingmentioning
confidence: 99%
“…In RT, the concepts of ray optics are used to solve Maxwell's equations asymptotically in the high frequency regime [84]. In comparison to full-wave methods of solving Maxwell's equation, RT achieves accurate results within reasonable computation time when the propagation scenario is several orders greater than the wavelength of the electromagnetic wave [85], [86]. Depending on the electrical and geometrical characteristics of the objects in the digital map, a ray might undergo reflection, diffraction, penetration, diffuse scattering or attenuation by vegetation.…”
Section: Interaction Mechanismsmentioning
confidence: 99%